1995
DOI: 10.2494/photopolymer.8.461
|View full text |Cite
|
Sign up to set email alerts
|

Surface reaction of laser-ablated polyester films with vinyl derivatives.

Abstract: The formation of radicals on the surface of poly(ethylene naphthalate) (PEN) and poly(ethylene terephthalate) (PET) films after KrF excimer laser ablation was investigated by measurements of electron spin resonance (ESR) and by analyses of surface reaction with a vinyl monomer at a cryogenic temperature. The ESR spectrum of the ablated films in a sealed tube showed a broad peak. Acrylic acid ester and styrene derivatives were immobilized on the ablated and fragment-deposited surfaces through chemical bonds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1997
1997
2001
2001

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…18 Niino et al reported that irradiation by the KrF laser generated reaction is similar to the conventional photodegradation where the ester bond is cleaved through radicals on the PET film surface although the lifetimes of the radicals were short. 5 Kokai conducted a Norrish type I reaction; then, it decomposed into smaller fractions. The oxygen loss recorded by the a similar experiment using irradiation energy above the 200 mJ/cm 2 fluence, and ionic frag-O/C ratio at the fusion layer can be attributed to the loss of small gaseous molecules such as CO ments were observed in addition to neutral fragments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 Niino et al reported that irradiation by the KrF laser generated reaction is similar to the conventional photodegradation where the ester bond is cleaved through radicals on the PET film surface although the lifetimes of the radicals were short. 5 Kokai conducted a Norrish type I reaction; then, it decomposed into smaller fractions. The oxygen loss recorded by the a similar experiment using irradiation energy above the 200 mJ/cm 2 fluence, and ionic frag-O/C ratio at the fusion layer can be attributed to the loss of small gaseous molecules such as CO ments were observed in addition to neutral fragments.…”
Section: Discussionmentioning
confidence: 99%
“…been reported. 4,5 We have studied the laser ablation phenomena from the viewpoints of morphology, 6 surface Irradiation with Excimer Laser chemical structure, and surface properties. [7][8][9] Irradiation was carried out with a KrF excimer la-PET film is a suitable material for studying the ser (248 nm) (Lambda-Physik Model LPX120icc) laser ablation since the mechanism of photochemfilled with a mixture of Kr, Ne, and F 2 gases.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, there have been many reports of surface modification4–9 when excimer lasers irradiate polymer fibers and films. The special feature of our research is that we have also made use of a photochemical process that is specific to the excimer laser, an ultraviolet light with sharp monochromatism and high intensity, and have investigated the processing and modification of the surface of poly(ethylene terephthalate) (PET) films and fibers 10–13.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13] Nevertheless, little attention has been given to application of this technique to preparation of organic thin films. However, since Hansen et al reported the preparation of polymer films consisting of the same components as the target polymer materials using laser ablation for the first time [14], deposition of organic films by laser ablation [15][16][17][18] has gradually come into notice and to be considered as a good method for the preparation of novel functional organic thin films in view of the possible control of their chemical structures by selection of wavelength and fluence of the laser beams applied for ablation.…”
Section: Introductionmentioning
confidence: 99%